Biblical Christianity in Modern Africa - O'Donovan, Wilbur (Paternoster, 2000)
Biblical Christianity in Modern Africa describes the major issues facing the church in Africa and offers suggestions on how these problems can be overcome. The church in Africa urgently needs to return to biblical Christianity. Churches are plagued with nominal Christians, false miracle workers, modern day Pharisees, and false teaching of many kinds. Marriages and families are in great need of family life teaching based on the Bible rather than culture. The church is consumed with conflict, denominationalism, and division. All of this has kept the church from being the greatest force on earth for good and for God in a sick and sin-filled world. The church is in need of revival - a revival based on obedience to the Word of God that will bring reconciliation, love, and unity to God's people.